2012
DOI: 10.1002/ccd.24374
|View full text |Cite
|
Sign up to set email alerts
|

Impact of different stent alloys on human vascular response to everolimus‐eluting stent: An optical coherence tomography study: The OCTEVEREST

Abstract: Background New generation drug‐eluting stents (DES) incorporate thinner struts and novel alloys to improve clinical performance. Nevertheless, the impact of novel stent materials and designs on human vascular response to DES remains elusive. We sought to evaluate the in‐vivo coronary artery response to platinum‐chromium (PtCr) versus cobalt‐chromium (CoCr) stents featuring the same durable polymer and antiproliferative drug by optical coherence tomography (OCT). Methods and Results A total of 42 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 27 publications
2
9
1
Order By: Relevance
“…Compared with first-generation DES, new generation DeS with thinner stent platforms, biocompatible polymers and rapid drug elution were designed to facilitate earlier anatomical and functional healing of stented vessels. The current study showed that struts were still inadequately covered in the PtCr-eeS group at 2-month follow-up, which is consistent with previous reports: a similar study comparing neointimal coverage by OCT at 6 months reported equivalent rates of uncovered struts between PtCr-eeS and CoCr-eeS (8.46 and 5.88 %, respectively) [20]. another, larger multi-centre study comparing PtCr-eeS and CoCreeS in 12-month clinical follow-up showed non-inferiority of the PtCr-eeS regarding target vessel failure [21].…”
Section: Invasive Hemodynamic Measurementssupporting
confidence: 94%
“…Compared with first-generation DES, new generation DeS with thinner stent platforms, biocompatible polymers and rapid drug elution were designed to facilitate earlier anatomical and functional healing of stented vessels. The current study showed that struts were still inadequately covered in the PtCr-eeS group at 2-month follow-up, which is consistent with previous reports: a similar study comparing neointimal coverage by OCT at 6 months reported equivalent rates of uncovered struts between PtCr-eeS and CoCr-eeS (8.46 and 5.88 %, respectively) [20]. another, larger multi-centre study comparing PtCr-eeS and CoCreeS in 12-month clinical follow-up showed non-inferiority of the PtCr-eeS regarding target vessel failure [21].…”
Section: Invasive Hemodynamic Measurementssupporting
confidence: 94%
“…While the percent of uncovered struts was lower for ZES, 2.1% vs 0.5%, both stents had a low percent of uncovered struts. Strut coverage with APSES is at least comparable, if not numerically higher than with other DES evaluated by the same core laboratory 26,27 .…”
Section: Discussionmentioning
confidence: 58%
“…The results of OCT analysis were reported on per-patient summaries rather than per-strut. While this approach to OCT data analysis may have limitations, this method is commonly used in reporting OCT results and allows comparability with previously reported studies 26,27 . The main limitation is that lesions with uncovered areas of exactly the same size will weight differently in the analysis depending on the total stented length.…”
Section: Study Limitationsmentioning
confidence: 99%
“…In our registry, OCT analysis of the Supraflex SES showed 98.1% strut coverage at 6 months, while it was 91.5% and 94.1% in the PROMUS Element and XIENCE DES, respectively. 28 The Supraflex SES had a favourable healing index of 4.8 (1.0-22.9). Lack of healing and absence of endothelial cell coverage of the stent struts have been strongly associated with DES late thrombosis in human autopsy studies.…”
Section: Discussionmentioning
confidence: 95%